Real-time heat capacity measurement during thin-film deposition by scanning nanocalorimetry - Zhang, M.; Yu. Efremov, M.; Olson, E.A.; Zhang, S.Z.; Allen, L.H.
The scanning nanocalorimetry technique is utilized to characterize thin-film growth in real-time. The technique generates three-dimensional heat capacity data as a function of temperature and thickness that show the continuous change of indium film during deposition. The measurement interval is ;431023 nm in thickness. Indium thin films form nanoparticles on silicon nitride surfaces that show the phenomena of melting point depression and the formation of magic number size particles. The measured increment of the heat capacity DCp is ;30 pJ/K and the temperature resolution is better than 0.5 K.